Five go adventuring again - Blyton, Enid (Hodder Children's London, 2001)
The Famous Five--Julian, Dick, Anne, George, and Timmy--are determined to find out who is responsible for the thefts at Kirrin Cottage and the discovery of an old map and a very unusual hiding place point to a suspect